In my class we are working on Literal Equations and Formulas.

Thank you for the opportunity to help you with your question!

So because we are being asked to solve for various values of y when x is equal to something, we need to rearrange the equation:

-5y = 9-3x

y = -(9-3x)/5

So, plug in those three values!

For x=-1, y = -(9-3*-1)/5 = -(9--3)/5 = -12/5

For x=0, y = -(9-3(0))/5 = -9/5

For x=1, y = -(9-3(1))/5 = -6/5

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up